2001
DOI: 10.1161/hc3501.093798
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Sarco/Endoplasmic Reticulum Ca 2+ Uptake Activity Can Account for the Reduced Response to NO, but Not Sodium Nitroprusside, in Hypercholesterolemic Rabbit Aorta

Abstract: Background-Hypercholesterolemia (HC) impairs acetylcholine-induced relaxation but has little effect on that caused by the NO donor sodium nitroprusside (SNP), suggesting that acetylcholine releases less NO from the endothelium in HC. The relaxation to authentic NO gas, however, is also impaired in HC aortic smooth muscle, indicating an abnormal smooth muscle response. NO relaxes arteries by both cGMP-dependent and -independent mechanisms, and the response involves calcium (Ca 2ϩ ) store refilling via the sarco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
40
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 32 publications
3
40
1
Order By: Relevance
“…24,25 This process is, at least partially, cGMP independent. 19,25 Moreover, we have shown that HC impairs SERCA function and decreases the cGMPindependent SERCA-dependent smooth muscle response to NO. 19 The reduced SERCA activity in HC is not due to decreased SERCA protein levels.…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…24,25 This process is, at least partially, cGMP independent. 19,25 Moreover, we have shown that HC impairs SERCA function and decreases the cGMPindependent SERCA-dependent smooth muscle response to NO. 19 The reduced SERCA activity in HC is not due to decreased SERCA protein levels.…”
mentioning
confidence: 97%
“…NO activates guanylyl cyclase and relaxes arteries, and its activity is preserved at least during the early stages of HC. 19,21,22 Thus, sodium nitroprusside-induced relaxations that depend on the activation of guanylyl cyclase and those caused by 8-bromo-cGMP are preserved in HC. 19 K ϩ channels are directly activated by NO 23 ; however, K ϩ channelmediated relaxation by NO is preserved in HC carotid arteries.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Additional evidence supports a role for cGMP-independent activation of delayed rectifier K ϩ channels in pulmonary arterial smooth muscle cells (32). Other direct effects of NO include stimulation of SERCA in rabbit aortic smooth muscle, leading to increased Ca 2ϩ reuptake by intracellular stores, a fall in [Ca 2ϩ ] i , and consequent inhibition of store-operated Ca 2ϩ influx (1,2,9). This latter mechanism of cGMP-independent activation of SERCA is consistent with the findings of Mingone et al (16), which identify regulatory influences of hypoxia on this pathway.…”
mentioning
confidence: 89%